Nurses' perception about their role in reducing health inequalities in community contexts - Jorge Sotelo-Daza; Yaneth Esperanza Jaramillo; Martha Vivas Chacón (Universidade de São Paulo, 2024)
Abstract Objective: to understand nurses' perception about their role in reducing health inequalities in community contexts. Method: a qualitative study with a phenomenological approach addressed from Heidegger's Interpretive Theory and the health inequality settings. A total of 18 in-depth interviews were conducted with nurses working in health institutions devoted to community interventions. The following five-phase process was adopted for the qualitative data analysis: Accumulation; Disassembling; Reassembling; Interpretation; and Conclusion. Results: four main topics that nurses mobilize to mitigate health inequalities in community settings were identified, namely: Competences to create, operationalize, monitor and assess health policies; Leadership and management for health and care processes at the individual and collective levels; Professionals that devise care strategies; and Care approach based on characteristics of the territory. Conclusion: nurses perceive that their role contributes significantly to reducing health inequalities in community settings based on the creation, operationalization, monitoring and assessment of health policies. From the sociocultural, economic and political characteristics of the territory, they prioritize actions in disadvantaged human groups in order to improve access, opportunities, continuity and quality in health.